DETECT AND MITIGATE MALWARE THREATS USING SANDBOXING TECHNOLOGY - Ade Andryani; Tata Sutabri (Sean Institute, 2023)
As sandboxing grows in popularity as a method of malware detection and prevention, cybercriminals will find new ways to circumvent this technology. For example, there are new types of malware that can recognize if they are in a sandbox. These malware infections do not execute their malicious code until they are outside the sandbox. One of the techniques attackers use to circumvent a sandbox solution is Lack of Users input. In this malware can analyze user input level to detect sandbox. In contrast to a sandbox, different types of user activity, such as mouse or keyboard activity occur frequently. Implementation of sandboxing technology in testing and analyzing malware behavior, including malware that uses data obfuscation techniques, can provide a better understanding of the characteristics and behavior of the malware. Effective mitigation measures include blocking malware access to system resources and turning off malware execution completely.